Maternal and Umbilical Cord Heat-Shock Protein 70 Levels in Patients with Gestational Diabetes Mellitus - Aybike Tazegul; Sedat Abuşoğlu; Görkem Aktaş; Nasuh Utku Doğan; Berat Berrin Gençoğlu Bakbak; Cetin Celik; Ali Unlu; Özlem Seçilmiş; Ayşegül Kebapçılar; Setenay Yılmaz; Mete Bertizlioğlu (Genel Tıp Dergisi)
AIMS: The purpose of this study is to determine if heat shock protein 70 (Hsp-70), a marker of cellular stress, is elevated in maternal serum and umbilical cord in pregnancies complicated by gestational diabetes mellitus (GDM) and to determine whether altered serum Hsp-70 concentrations in umbilical cord are related to serve as an indicator of early term delivery (37 0/7–38 6/7 weeks of gestation) in women with GDM and control group. METHODS: The study included 62 patients with GDM (GDM group) and 22 non-diabetic, healthy women before caesarean section in this case-control study. We analyzed serum levels of Hsp-70 in pregnancies and umbilical cord sera and other biochemical and anthropometric markers, early term delivery in all subjects. RESULTS: Maternal Serum levels of Hsp-70 were significantly higher in patients with GDM than in healthy pregnant women. The umbilical cord levels of Hsp-70 in GDM patients were also increased as compared to healthy pregnant women but missed the commonly acceptable significance level. Cord Hsp-70 levels showed a negatively significant correlation with time of delivery, in women with GDM patients. Cord Hsp-70 levels showed a negatively significant correlation with time of delivery, also in the whole group. CONCLUSIONS: Maternal Hsp-70 was significantly higher in patients with GDM. The obtained results seem to indicate that elevated umbilical cord Hsp-70 values may potentially be used as indicators of risk factor for early term delivery in pregnancies.